Absorptive capacity of the cluster resources and the local buzz promoted by partnering among goatish producers at Cariri Paraibano region - Moreira, Vinicius Farias; Chim-Miki, Adriana Fumi; Oliveira, Keyse Fonseca (Revista de Administração da UFSM, 2020)
Purpose – This paper contributes to the literature on local buzz and the absorptive capacity of firms aiming the competitiveness of the local productive agglomerations. The associations of producers of goat's milk and derivatives of Cariri Paraibano were analyzed. They form a cluster of 881 partners and are responsible for the production of approximately 8,631 liters of goat milk per day. The research objective was to identify, based on the local buzz, the participants' awareness about the clustering benefits and the absorption of cluster resources. Design/methodology/approach – It used a qualitative methodology based on a case study. Various sources of evidence were used to guarantee the reliability of results. So, it performs triangulation of in-depth interviews, direct observation, and content analysis of documents. Findings – The results indicated the existence of knowledge about goat production, a similar level of absorptive capacity between the producer associations, and a degree of awareness of the advantages of being agglomerated. Also, findings evidenced external knowledge not absorbed by the producers that could be linked to the incompleteness of the association's role as cluster vectors. Originality/value – The sector dynamics depend on the organizations' view on the importance of information and its use in the operation of firms in order to increase their absorptive capacity.